Modern principles of conservative treatment of mild and moderate forms of ulcerative colitis - O. V. Golovenko (Лечащий Врач)
Ulcerative colitis is a chronic disease characterized by inflammation that usually begins in the rectum and diffusely spreads proximally, involving part or all of the colonic mucosa. The etiology of ulcerative colitis is still unknown, so there are no drugs that could cure this formidable disease. The entire vast arsenal of drugs that is offered for the treatment of ulcerative colitis is aimed at various, as yet insufficiently studied links in the pathogenesis of ulcerative colitis. The emergence of a new class of medicines (genetically engineered biological preparations), unfortunately, has not solved this cardinal problem. The only way to «cure» ulcerative colitis at present is to remove the entire colon with the formation of an ileoanal reservoir anastomosis or a permanent ileostomy. However, surgical treatment of ulcerative colitis is associated with many complications and sometimes death. The main goals of therapy for ulcerative colitis are to induce and maintain steroid-free clinical and endoscopic remission, reduce the incidence of complications, disability and improve the quality of life. Severe forms of ulcerative colitis requiring hospitalization and intensive conservative treatment, and sometimes surgery, account for about 15% of all cases of ulcerative colitis. Most mild to moderate forms of ulcerative colitis can be successfully treated on an outpatient basis with conventional medicines, most notably the innovative mesalazine. A competent combination of oral and rectal forms of mesalazine allows in most cases to achieve not only clinical remission, but to achieve the modern goal of treating ulcerative colitis – healing of the colon mucosa, that is, endoscopic remission. The article presents modern views on the treatment of mild and moderate forms of ulcerative colitis with different extent of colon damage, which are reflected in the latest domestic and foreign guidelines.